The political economy of geographical indications - Koen Deconinck; Martijn Huysmans; Johan Swinnen (Katholieke Universiteit Leuven, LICOS Centre for Institutions and Economic Performance, 2015)
In this article we study the political process that governs the creation and size of new Geographical Indications (GIs). Producers can choose to apply for a GI and subsequently go through a bargaining process with the government. We derive the optimal GI area from the point of view of consumers, producers, social welfare, and the government; and we show how bargaining leads to a GI size in between the applicant's optimum and the government's optimum. Under the assumption that the non-GI good is a commodity, any GI implemented through the political process is welfare-enhancing, but not all welfare-enhancing GIs will be proposed by producers.
Keywords: 330